(3GdOQI GdeVjI aj GdbQGAGJ GdKdGK GdeQVjIs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,(B833 (3g`s
(3ChdgG (B:s
(3bd GdMeO ddg GdPi hMOg YdG heLOg hSHd Yhfg hJhSO s
(3BNQgG (B:s
(3hef HLejY GdTed hGZaQ PfhHfG hUd Ydi NjQ GdCfGe hef JdG JeJ GdOQI GdeVjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3efXheIs
(3cJHJ GdYfGhjf HGdMeQIs
(3HChdgG Jedjc SfI (B1071(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs